Law on the Web : a guide for students and practitioners - Stein, S. D. (Stuart D.) (Prentice Hall, 2003)
Law on the Web is ideal for anyone who wants to access Law Internet resources quickly and efficiently without becoming an IT expert. The emphasis throughout is on the location of high quality law Internet resources for learning, teaching and research, from among the billions of publicly accessible Web pages. The book is structured so that it will be found useful by both beginners and intermediate level users, and be of continuing use over the course of higher education studies. In addition to extensive coverage on locating files and Web sites, Part III provides a substantial and annotated list o.